PERBEDAAN PENGETAHUAN, SIKAP, DAN PRAKTIK KESEHATAN REPRODUKSI SISWA DI DUA SMK YANG TERPAPAR PEER EDUCATION DI KOTA SEMARANG TRIWULAN II TAHUN 2016 - Kadina Alifianur; Dharminto Dharminto; Sri Winarni (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2016)
PKBI study in 2012 mentioned that 43,22% of adolescent knowledge about reproductive health remains low. As one of the access provider adolescent reproductive health services, PKBI establish Peer Education so teenagers received the right information. From 6 schools, 2 SMK been making peer education as extracurricular but only 1 that still active. The purpose of this research is to analyze the differences in knowledge, attitudes, and practices of reproductive health in two SMK that exposed peer education in Semarang. The type of this research is explanatory research with a cross sectional study design. The population in this study amounted to 381 peoples, as many as 143 peoples from SMK which actively implementing Peer Education and 238 peoples from SMK which less actively. By using simple random sampling was obtained sample 35 peoples from each SMK. Data analysis consists of univariate analysis by presenting the frequency tables and bivariate analysis using the Mann-Whitney test to see differences in knowledge, attitudes, and practices of reproductive health respondents. Descriptive analysis showed that the knowledge, attitudes, and practices of reproductive health respondents from SMK which actively implementing peer eduation, is better than respondents from SMK which are less active. The results of the statistical test showed that there are differences in knowledge in two SMK that exposed peer education actively and less actively (p-value = 0.015), there are differences in attitudes in the two SMK that exposed peer education actively and less actively (p-value = 0.000 ), and there are differences in practices in two SMK that exposed peer education actively and less actively (p-value = 0.017). It is necessary to developt the learning about reproductive organs and HIV/AIDS, and for SMK that less actively implementing peer education to improve the implementation of the program in once a week